(untitled) (Wire Insights: Journal of Innovation Insights, 2025)
This article examines the scientific and educational views of Mahmudkhoja Behbudi and their historical as well as contemporary significance. It explores Behbudi’s ideas on education, national awakening, enlightenment, and social reforms, emphasizing their relevance for educating today’s youth. The study also highlights the impact of Behbudi’s pedagogical and educational concepts on the modern educational process.